PELATIHAN MERANCANG ASESMEN HASIL BELAJAR DI LBB TAMAN PINTAR LAMONGAN - Hadi Suryanto; Yayuk Chayatun Machsunah; Ratna Nurdiana (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
The Learning Guidance Institute (LBB) Taman Pintar Lamongan is a non-formal educational institution. Even though it is non-formal education, the assessment of learning outcomes for students must still be considered like formal education. The choice of Taman Pintar as a place for Community Service for us lecturers at PGRI Adi Buana University, Lamongan Campus, is inseparable because Taman Pintar is an institution that uses graduates on our campus as tutors in the last 10 years